MECHANICAL PROPERTIES OF PETG-BASED MATERIALS DESTINED FOR 3D-PRINTING - Plamadiala, Ioan; Croitoru, Catalin; Pop, Mihai Alin (Acta Technica Napocensis, 2023)
Polyethyleneterephthalate glycol (PETG) and poly (lactic acid) (PLA) stand out as two leading 3D printing filaments. PETG boasts exceptional strength, durability, chemical resistance, and UV light resilience. Meanwhile, PLA is celebrated for its ease of use and biodegradability. This research delves into a comparison of their mechanical attributes and 3D-printing performance, spotlighting PETG's advantages in various applications. PETG shines by withstanding higher temperatures, resisting chemicals and UV rays, and offering greater flexibility compared to PLA. Moreover, PETG showcases superior layer adhesion and reduced warping, resulting in top-notch prints. Our comprehensive study data underscores PETG's excellence in flexural strength (3 MPa), compression strength (61 MPa), and dimensional stability. PETG emerges as the superior choice for applications demanding robustness, endurance, and environmental resistance.
Keywords: 3D-printing; Polyethyleneterephthalate glycol; poly (lactic acid); mechanical properties